2014
DOI: 10.1108/jcm-10-2013-0725
|View full text |Cite
|
Sign up to set email alerts
|

The impact of economic perceptions on status consumption: an exploratory study of the moderating role of education

Abstract: Purpose – Given the economic downturn, the purpose of this study was to determine if a relationship exists between economic perceptions and consumers' motivation to consume for status and if this relationship was moderated by education level. Design/methodology/approach – A stratified random sample of adult consumers in the southeastern USA were surveyed by telephone. The hypotheses were tested utilizing structural equation modeling. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…To analyse the movement of the consumer confidence index, we divided the analysis into two separate models: Islamic financial sector indicators and conventional financial sector indicators. The consumer confidence index has been proven to be one of the most influential variables in consumption decisions and in the economic situation (Bock et al;Sorić, 2018). From logistic regression model results shown in Table 9, it can be concluded that statistically the JII index, Islamic bank capital, gold price, economic growth and USD exchange rate have negatively and significantly affected the changes of in the consumer confidence index.…”
Section: Probit Logit Model Robustness Standard Errormentioning
confidence: 95%
See 1 more Smart Citation
“…To analyse the movement of the consumer confidence index, we divided the analysis into two separate models: Islamic financial sector indicators and conventional financial sector indicators. The consumer confidence index has been proven to be one of the most influential variables in consumption decisions and in the economic situation (Bock et al;Sorić, 2018). From logistic regression model results shown in Table 9, it can be concluded that statistically the JII index, Islamic bank capital, gold price, economic growth and USD exchange rate have negatively and significantly affected the changes of in the consumer confidence index.…”
Section: Probit Logit Model Robustness Standard Errormentioning
confidence: 95%
“…The consumer confidence index is a monthly report detailing with consumer attitutes and buying intentions, with data available by age, income and region. The index has proven to be one of the most influential variables in consumption decisions and in the economic situation (Bock Eastman, & McKay, 2014;Sorić, 2018). Consumer confidence is influenced by their personal finances and the economic environment, macroeconomic conditions and the business situation (Ferrer et al 2016;Salhin, Sherif, & Jones, 2016;Li, Guo, & Park, 2017).…”
Section: Consumer Confidence Indexmentioning
confidence: 99%
“…Social comparison, social adjustive attitude, symbolic consumption were topics that included. (Elizabeth Bock et al, 2014;Chan et al, 2015;Brun and Castelli, 2016;Zhang et al, 2019;Shao et al, 2019aShao et al, , 2019bChen et al2021;Wang et al, 2021) Since Veblen's (1899) study on conspicuous consumption, the extrinsic value was recognized as a major motivation during the purchase of luxury products. In recent years, Yuan et al (2021) explained the similarities and differences between conspicuous consumption and luxury consumption.…”
Section: General Consumer Motivationmentioning
confidence: 99%